Using administrative data to inform operational and policy developments relating to family homelessness in the Dublin Region - Morrin, Holly; O'Donoghue Hynes, Bernie (International Journal of Population Data Science, 2018)
Background Since 2014 Ireland has seen an unprecedented growth in the number of families being accommodated in emergency accommodation, particularly in the Dublin Region. Indeed, family homelessness has become an issue of concern across Europe but there is also a widespread lack of data about the specific situation of homeless families (Baptista et al., 2017). Objectives This research uses administrative data to address this gap in knowledge and provide robust quantitative data on trends in family homelessness in the Dublin Region. Methods The research was compiled using a combination of PASS data and data recorded from assessment forms completed with homeless clients by the housing sections in the four local authorities across the Dublin region. PASS, the national shared services database for all state funded NGO and local authority homeless services has uniquely allowed for analysis of data relating to the entire population of families newly experiencing homelessness in the Dublin Region since January 2016. Findings Dedicated data collection and analysis of such administrative data has produced interesting findings covering not only profiles and reasons for family homelessness but also families’ rates of progression through homeless services. Of note was that one in six families departed homeless services without active engagement with support services, a figure previously unreported. Conclusions The combined use of administrative and PASS data gives a more complete picture of patterns of service use and engagement with homeless services among families newly experiencing homelessness. Detailed findings were passed on to operational staff to both plan for services to support families experiencing homelessness and to assist in developing a regional and national response to the issue of housing supply.